Millennial‐scale variability to 735 ka: High‐resolution climate records from Santa Barbara Basin, CA. (30th May 2013) - White, Sarah M.; Hill, Tessa M.; Kennett, James P.; Behl, Richard J.; Nicholson, Craig
<x xml:space="preserve">Abstract</x> [1] Determining the ultimate cause and effect of millennial‐scale climate variability remains an outstanding problem in paleoceanography, partly due to the lack of high‐resolution records predating the last glaciation. Recent cores from Santa Barbara Basin provide 2500–5700 year "windows" of climate with 10–50 year resolution. Ages for three cores, determined by seismic stratigraphic correlation, oxygen isotope stratigraphy, and biostratigraphy, date to 293 ka (MIS 8), 450 ka (MIS 12), and 735 ka (MIS 18). These records sample the Late Pleistocene, during which the 100 kyr cycle strengthened and the magnitude of glacial‐interglacial cyclicity increased. Thus, these records provide a test of the dependence of millennial‐scale behavior on variations in glacial‐interglacial cyclicity. The stable isotopic (δ18O) composition of planktonic foraminifera shows millennial‐scale variability in all three intervals, with similar characteristics (duration, cyclicity) to those previously documented during MIS 3 at this site. Stadial G. bulloides δ18O values are 2.75–1.75‰ (average 2.25‰) and interstadial values are 1.75–0.5‰ (average 1‰), with rapid (decadal‐scale) interstadial and stadial initiations of 1‐2‰, as in MIS 3. Interstadials lasted 250–1600 years and occurred every 650–1900 years. Stadial paleotemperatures were 3.5–9.5°C and interstadial paleotemperatures were 7.5–13°C. Upwelling, evidenced by planktonic foraminiferal assemblages and δ13C, increased during interstadials, similar to MIS 3; high productivity during some stadials was reminiscent of the Last Glacial Maximum. This study builds upon previous records in showing that millennial‐scale shifts were an inherent feature of Northern Hemisphere glacial climates since 735 ka, and they remained remarkably constant in the details of their amplitude, cyclicity, and temperature variability.